FEATURES OF DUAL EDUCATION AND SIGNIFICANCE IN PRODUCTION (World Economics and Finance Bulletin, 2024)
The article analyzes the current features of dual education. It is advisable to introduce dual education into the educational process of vocational education. The advantages of dual education in the field of higher education, the formation of specialist skills and its importance today are also comprehensively substantiated